Retrospective analysis after endoscopic urethral injections of glutaraldehyde‐cross‐linked‐collagen or dextranomer/hyaluronic acid copolymer in bitches with urinary incontinence. (2nd November 2018) - Lüttmann, K.; Merle, R.; Nickel, R.
Abstract : Objectives: To evaluate the outcome of endoscopic injection of two different bulking agents, glutaraldehyde cross‐linked collagen and dextranomer/hyaluronic acid copolymer into the urethral submucosa in female dogs with urinary incontinence caused by urethral sphincter mechanism incompetence. Materials and Methods: Retrospective review of records and follow‐up communication with owners of dogs that received an endoscopically guided urethral bulking procedure. In each dog, either cross‐linked collagen (2007 to 2011) or dextranomer/hyaluronic acid copolymer (2012 to 2015) was used. At least three injections were made in a circular arrangement in the midurethral region until the urethral lumen was closed. Results: Complete questionnaires were available from 50 of 100 pet owners. The mean interval between the treatment and interview was 67 (range: 57 to 114) months in the cross‐linked collagen group and 19 (range: 2 to 48) months in the dextranomer/hyaluronic acid copolymer group. The mean duration of continence was 45∙8 months (range: 12 to 84 months) in the cross‐linked collagen group and 20∙5 months (range: 12 to 48 months) in the dextranomer/hyaluronic acid copolymer group. The success rate at 6 months or more after the procedure was 71% after the injection of cross‐linked collagen and 58% after injection of dextranomer/hyaluronic acid copolymer. One minor complication (transient haematuria) occurred in one dog. There were no major complications. Clinical Significance: Urethral injection of dextranomer/hyaluronic acid copolymer in bitches with urethral sphincter mechanism incompetence is a useful alternative to cross‐linked collagen injection, which is no longer available in the European market. Dextranomer/hyaluronic acid copolymer injection is a minimally invasive alternative to surgical procedures and has a low complication rate.